Customers perception of credit card marketing strategies and its relationship with credit card usage among Malaysians - Kassim, Salina; Hussin, Siti Rahayu; Jamal, NurAien (2012)
This study aims to explore the impact of marketing strategies undertaken by the credit card providers on credit card usage. To evaluate the existing marketing strategies by the credit card providers, specific questions on customers perceptions regarding credit card product, promotional, pricing and place strategies (such as branding, reputation, advertisements, sales promotions, direct marketing strategies and finance charges) were designed. Meanwhile, credit card usage patterns were measured with questions on card possession, usage frequency, spending amount and usage motivation adapted from Kara et al., 1994. The study adopts a quantitative research approach through survey questionnaires and interviews in linking marketing strategies to credit card usage. Additionally, logistic regression was performed on the data to determine if there are any relationships between marketing strategies of the credit card providers with credit card usage. The results of this study would provide significant inputs to policy makers to better understand the credit card usage in Malaysia.